EMPLOYING TWITTER IN THE U.S. PRESIDENTIAL ELECTION CAMPAIGN IN 2016: U.S. PRESIDENTIAL CANDIDATE DONALD TRUMP’S TWEETS AS A “MODEL”: (A Research Drawn from a Master’s Thesis) (An Analytical Study) - Hamid Zamil, Muhammad; خورشيد مراد كامل (ALBAHITH ALALAMI, 2019)
This study aimed to identify the employment of the social networking platform «Twitter» in the 2016 presidential campaign led by the Republican candidate, Donald Trump; and analyse his tweets through his personal account on «Twitter» for the period from: 10/ 8/2016 to: 11/ 8/2016 which represents the last month of the election campaign. The study belongs to the type of descriptive studies using the analytical method through an analysis index that includes sub-categories and other secondary categories. The research has adopted the ordinary unit of information material (tweet) as an analysis unit for this purpose. The validity of the tool was verified by a precise definition of the units of analysis and the analysis tool was presented to a group of experts for arbitration. The Holistic Equation was, in addition, used to verify the reliability of the analysis tool. The results showed that the field of elections is the most focused area on which President Trump focused. The domestic policy issues came second, while the content of encouraging participation in the elections came out the contents covered by the tweets. Accusations of corruption by Trump against his Democratic opponent, Hillary Clinton, came second in the category of contents. As for the targeted parties, the study showed that the American voters are the most targeted group followed by the personality of Hillary Clinton. In the category of techniques, it appeared that the technique of encouragement is the most used. Then, it was followed by the technique of criticism. As for the means of support, it was noted that the most used was the image, then the websites link.